Nursing Student and Faculty Narratives During COVID-19 Pandemic: Challenges and Recommendations From a Canadian Perspective - Brenda Orazietti RN, BScN, MEd, MScN, CCNE, CCSNE; Sandra Peniston RN (EC); Zubaida Mohammed RN (EC); Hermila Demelie BScN Candidate; Jemina Frances Duldulao BScN Specialized Hons Candidate; Misbah Rao BSc, MEd, BScN Candidate (SAGE Publishing, 2023)
Introduction Worldwide, COVID-19 affected nursing students' and faculty's mental and physical health. The final clinical placement for fourth-year nursing students during the third wave of COVID-19 in Toronto, Canada, included direct patient care without vaccination eligibility. Students' experiences during the pandemic and faculty exposure to teaching and supporting them provide unique reflective opportunities. Objective To examine the lived experiences of nursing students and faculty during the third wave of the COVID-19 pandemic. Methods The study used a qualitative phenomenological design with thematic analysis. A voluntary response sample of 80 participants shared their narratives of working and teaching during January to May 2021. An optional interview guide offered open-ended questions requiring reflection. The study was conducted in a nursing school in Toronto, Canada during fourth-year baccalaureate students final clinical placement settings. Results A total of 77 fourth-year baccalaureate nursing students and three faculty members participated. Thematic analysis of nursing student narratives identified four main themes: (i) fear and anxiety of COVID-19 during clinical practice; (ii) impact on students' learning environments; (iii) intrinsic and extrinsic factors that enabled students to persevere; and (iv) how to deal with future pandemics. Thematic analysis of faculty narratives identified three main themes: (i) the importance of preparatory work; (ii) psychological and physical manifestations of supporting students; and (iii) the resilience of students and faculty. Conclusion Future disease outbreaks and other large-scale health events will require nurse educators to understand and plan strategies for both themselves and students practicing in high-risk clinical settings. Nursing schools should rethink all fourth-year students' experiences, perceptions, and feelings to minimize their susceptibility to physical and psychological distress.